2003
DOI: 10.3904/kjim.2003.18.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Plasmodium Vivax Malaria

Abstract: Background:Since its reemergence in 1993, a number of cases of Plasmodium vivax malaria have been reported in Korea. We analyzed the cases of malaria patients living in Chuncheon and its neighboring communities, to characterize its clinical manifestations and laboratory findings, and to identify any differences between our clinical findings and those of previous studies.Methods:We reviewed the clinical records of cases that were confirmed as malaria by peripheral blood smear at Chuncheon Sacred Heart Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 6 publications
4
19
2
4
Order By: Relevance
“…In contrast, in temperate areas, relapses are fewer and delayed, and the haematological impact of each recurrence is less (Song et al . ; Goller et al . ; Price et al .…”
Section: Pathogenesis Of Disease In Vivax Malariamentioning
confidence: 99%
“…In contrast, in temperate areas, relapses are fewer and delayed, and the haematological impact of each recurrence is less (Song et al . ; Goller et al . ; Price et al .…”
Section: Pathogenesis Of Disease In Vivax Malariamentioning
confidence: 99%
“…Although a few studies targeting civilians in the Republic of Korea have been conducted since the re-emergence of malaria, most of the studies analyzed a small group of patients [7, 8]. This study is aimed at analyzing clinical features of vivax malaria and characteristics of recurred malarial patients who were treated at a hospital located in the northwestern part of Gyeonggi province where malaria is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia was a prominent finding in 75% of the cases at diagnosis, which resolved during therpy. 13 Memon et al when studying thrombocytopenia in hospitalised patients found (70%) patients had thrombocytopenia. 93% patients with thrombocytopenia were P. falciparum positive and only 7% patients had vivax malaria.…”
Section: Discussionmentioning
confidence: 99%